Gniazdo czasownika "mniemać" w historii języka polskiego - Knapik, Kinga (Wydawnictwo "Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The article presents the history of the word family of the lexeme "mniemać". The applied nest method, worked out by synchronic linguistics, has made it possible to gather and juxtapose lexical units in a diachronic perspective. The nest analysis is preceded with information on the etymology of words. Thus constructed “historical nests” show a different development path for the two following verbs, synonymous in Old Polish: "mniemać" and "mnieć". The verb "mniemać" has become obsolete now, whereas mnieć is a component word in modern compounds thanks to the form "po-mnieć", which is rarely used today but which was very active in the word formation in the Old and Middle Polish period. This form has become a basic signifier for numerous prefixal formations such as "przypomnieć", "upomnieć", "wspomnieć", "wypomnieć" and "zapomnieć". A juxtaposition of the words recorded in historical dictionaries of the Polish language with the modern vocabulary allows us to show the changes and transformations in the vocabulary of the language that remain oblique from the synchronic perspective.
The word-nest of the verb "mniemać" in the history of the Polish language
Keywords: Leksykologia diachroniczna; Słowotwórstwo diachroniczne; Gniazdo słowotwórcze; Etymologia